Microglial Acid Sensing Regulates Carbon Dioxide Evoked Fear - Vollmer, Lauren Larke (Biol Psychiatry, 2016)
BACKGROUND: Carbon dioxide (CO(2)) inhalation, a biological challenge and pathological marker in Panic Disorder, evokes intense fear and panic attacks in susceptible individuals. The molecular identity and anatomical location of CO(2)-sensing systems that translate CO(2)-evoked fear remains unclear. We investigated contributions of microglial acid sensor T cell death associated gene-8 (TDAG8) and microglial pro-inflammatory responses in CO(2)-evoked behavioral and physiological responses. METHODS: CO(2)-evoked freezing, autonomic and respiratory responses were assessed in TDAG8-deficient ((−/−)) and wildtype ((+/+)) mice. Involvement of TDAG8-dependent microglial activation and pro-inflammatory cytokine IL-1β with CO(2)-evoked responses was investigated using microglial blocker, minocycline and IL-1β antagonist, IL- 1RA. CO(2)-chemosensitive firing responses using single-cell patch clamping were measured in TDAG8(−/−) and (+/+) mice to gain functional insights. RESULTS; TDAG8 expression was localized in microglia enriched within the sensory circumventricular organs (CVOs). TDAG8(−/−) mice displayed attenuated CO(2)-evoked freezing and sympathetic responses. TDAG8 deficiency was associated with reduced microglial activation and pro-inflammatory cytokine, IL-1β within the subfornical organ (SFO). Central infusion of microglial activation blocker, minocycline and IL-1β antagonist, IL-1RA attenuated CO(2)-evoked freezing. Finally, CO(2)-evoked neuronal firing in patch clamped SFO neurons was dependent on acid sensor TDAG8 and IL-1β. CONCLUSIONS: Our data identify TDAG8-dependent microglial acid-sensing as a unique chemosensor for detecting and translating hypercapnia to fear-associated behavioral and physiological responses, providing a novel mechanism for homeostatic threat detection of relevance to psychiatric conditions such as panic disorder.